Systemic Lupus Erythematosus. Ten years of follow up - BermÃºdez Marrero, Witjal Manuel; Vizcaino Luna, Yanelis; FustÃ© JimÃ©nez, Celestino; BermÃºdez Marrero, William Alejandro; GonzÃ¡lez Otero, Zoe Alina; HernÃ¡ndez GarcÃa, Margarita (Revista Cubana de Reumatología, 2019)
Introduction: systemic Lupus Erythematosus (SLE) is a relatively frequent disease of universal distribution. Its incidence varies according to the characteristics of the studied population such as age, gender and ethno. It is a chronic and autoimmune disease, which cause is not clear at all. Objective: to characterize clinically and epidemiologically the patients with systemic lupus erythematosus. Methods: A descriptive investigation of 112 patients with diagnosis of systemic lupus erythematosus assisted at Arnaldo Milián Castro University Hospital was carried out from January 2008 to December 2017. Results: patients between 30 and 39 years of age were the most representative with a higher incidence in the female sex. High blood pressure prevailed as previous history and coffee as toxic habit. There was a higher affection of the osteomyoarticular system followed by skin and mucosa. The combination of Prednisone and Azathioprine was the most used treatment. Infections were the main cause of death. Conclusions: systemic Lupus Erythematosus is present with major frequency in female young patients, with a high risk of systemic affection as well as presenting a life-threatening evolution secondary to infections.